Droplet Combustion and Thermogravimetric Analysis of Pure Coconut Oil, Clove Oil, and Their Mixture - Adhes Gamayel; MN Mohammed; Mohamad Zaenudin; Eddy Yusuf (Science and Technology Indonesia, 2022)
The droplet combustion and thermal behavior of pure coconut oil (PCO), clove oil, and their mixture were experimentally investigated. The mixture fuels were PCO and clove oil at the percentage of 10% based on volume (PCO-CO10). The experimental method uses droplet combustion and thermogravimetric analysis. The fuel droplet was suspended in the junction of k-type thermocouple and ignited by a coil heater. The ignition and combustion processes of droplets were recorded using a digital single-lens reflex camera at 25 fps. Thermogravimetric analysis with alumina crucible was prepared to investigate the thermal behavior of fuel. The result showed that the sequence of ovoid flame for PCO and PCO-CO10 take place until 0.4 second and 0.44 second, respectively. Complete combustion was explained in that sequence. The ovoid flame was formed when eugenol, terpene, and lauric acid were evaporated first in both PCO and PCO-CO10. Minimum ovoid flame takes place in clove oil due to soot tendency in the burning process that marked flame as the open tip. PCO-CO10 has the highest peak temperature due to the presence both of double carbon chains in fatty acid and aromatic ring structures, which were easy to decompose in high energy input. Clove oil was the lowest onset temperature, which indicates more volatile matter in this fuel and PCO has the highest thermal stability due to the fatty acid component in their fuel.